Smart battery charger / Muhammad Solahuddin Mohd Sayudzi & Muhammad Faiz Mohd Soffian - Mohd Sayudzi, Muhammad Solahuddin; Mohd Soffian, Muhammad Faiz (2015)
Nowadays charging of mobile phone has becoming a part of our daily activities. Higher power consumption of phone battery increases the need of charging. For example, people use their phone every minute to check out what is happening and this consumes lots of battery power. This charging activity consumes time and electricity. Due to this time consuming activity, people always forget to unplug their charger when it is already fully charged. This situation leads to the damage of the battery and shorten the lifespan. Moreover, it will consume more electricity than it should. Therefore in this project, Smart Battery Charger is proposed where solar panel is used in this charger. This battery charger can prolong the battery life and saving electricity usage. The battery charger utilizes LEDs to indicate the condition of the battery charger. Red LED indicate the charger is in standby mood meanwhile id yellow LED lights up, it indicates that the charger is in charging process where both standby and charging is shown by the LCD. Moreover, instead of using conventional power source like home power socket, this battery charger receive power from sustainable solar cell source since solar is eco-friendly and won't harm any other living things besides it is more systematic and reliable to its users out there.